Fabrication and mechanical testing of cellulose lattice interpenetrating phase composites - Kuek, Ryan Jian Xing (Nanyang Technological University, 2022)
Composites are becoming one of the most dominant materials used in every industry in the world. This is mainly due to the superior properties that it can achieve through the combination of two or more materials. The focus of this study is an Interpenetrating Phase Composite (IPC), which made use of an open octet truss lattice structure made of paper for the reinforcement phase, and epoxy as the matrix phase of the composite. IPCs are widely used in anti-collision applications, which will then require the IPC to have decent energy absorption property. As such, this study aimed to investigate on the factors affecting the energy absorption capabilities of the composite, where the sample orientation (iso-stress and iso-strain), and the relative density of the reinforcement phase constituted the variables of the experiment. Paper and epoxy were used in this study, due to their energy absorption, strength and ductile properties while still being light in weight. The result of this study suggests that the IPCs with lower relative density tested in the iso-stress condition can achieve a higher energy absorption efficiency, as compared to those tested in the iso-strain condition, or even those with higher relative density. However, IPCs with higher relative density demonstrated better compressive strength and modulus. Compared to the typical foams used in energy absorption applications, the IPC in this study managed to achieve better energy absorption capabilities, albeit at a higher mass density.